(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2017)
تهدف الدراسة إلى اختبار العوامل الدافعة للمريض في تحديد خياراته لمقدم خدمة الرعاية الصحية (عيادة خاصة أو مشفى عام أو خاص). وقد طبقت الدراسة على عينة إحصائية مكونة من 695 مبحوثاً في مدينة دمشق واستُخدم نموذج الانحدار المنطقي المتعدد لتحليل البيانات Multinomial Logit Model. وتوصلت الدراسة إلى النتائج التالية: - سمعة أو شهرة الوحدة الصحية (مقدم الخدمة) هي العامل الأكثر أهمية في عملية الاختيار. - كلما ازدادت تكلفة الخدمة، ازداد معه احتمال اختيار البديل الأكثر تكلفة. - كلما ازداد زمن الانتقال اللازم للوصول إلى البديل موضوع المقارنة انخفض احتمال اختياره. - كلما ازداد زمن الانتظار في المشفى الخاص، انخفض احتمال اختياره. - لا يوجد أثر ذو دلالة إحصائية للمتغيرات الديموغرافية للمرضى (العمر، الجنس، الدخل، وضع العمل، الحالة الاجتماعية) على قراراتهم بخصوص البديل المفضل لتلقي خدمات الرعاية الصحية. - لا يوجد أثر ذو دلالة إحصائية لزمن الانتظار في العيادة الخاصة على خيارات المريض. - تزداد الرغبة الحدية بالدفع بمقدار ( 1.41) من أجل كل درجة إضافية على مؤشر سمعة العيادة الخاصة و ( 0.07) من أجل توفير ساعة انتظار. - تزداد الرغبة الحدية بالدفع بمقدار ( 1.06) من أجل كل درجة إضافية على مؤشر سمعة المشفى الخاص - و ( 4.79) من أجل توفير ساعة انتظار. و توصي الدراسة بأنه يتوجب على مقدمي خدمات الرعاية الصحية العمل بجدية على رفع سوية أدائهم باتجاه تجسيد وتعزيز سمعتهم دون إهمال العوامل الأخرى كعامل المكان وإجراءات تقديم الخدمة وما تنطوي عليه من انتظار وتكلفة. The aim of the study is two folds. First, it aims at analyzing the factors affecting Patient’s choice of health service provider (Private clinic, public hospital, or private hospital). This study applies a multinomial logit model (MNL) to analyze patient’s choice, using a sample of 695 respondents drawn from Damascus City. Second, the study estimates the marginal willingness to pay for an extra gain from a specific change in each of the characteristics of health provider, such as reputation and waiting time. Analysis results were as follows: - Perceived reputation of the health provider is the most important factor affecting the patient’s choice of health provider. - Ironically, higher treatment cost is associated with higher probability of choosing the more expensive health provider alternative. - The choice of a specific health provider against another is negatively associated with associated commuting time. - Waiting time at the private clinic has no significant effect on patient’s choice of the private clinic. - Marginal willingness to pay for extra level on perceived reputation index of a private clinic is estimated at US1.41, and US0.07 for an extra hour saved of waiting time. - Marginal willingness to pay for extra level on perceived reputation index of a private hospital is estimated at US1.06, and US4.79 for an extra hour saved of waiting time. - Patient’s demographic characteristics have an insignificant effect on the choice of a specific health provider against another. The study recommends health providers to enhance the level of their professional reputation as it turned out to be the most crucial factor affecting patient’s choice, and at the same time keep on improving other factors such as internal procedures, waiting time, and location.